Keterlibatan Syaikh Yusuf Al-Qaradhawi dalam Persatuan Ulama Dunia: Studi Kasus pada International Union of Muslim Scholars - Muhammad Khirul Fatihin; Wildana Wargadinata (NALAR: Jurnal Peradaban dan Pemikiran Islam, 2023)
Yusuf Al-Qaradawi's involvement significantly contributed to creating unity among Muslims worldwide. One form of Muslim unity is manifested in regional and international organizations. This research examines the contribution of Yusuf Al-Qaradawi's involvement in the World Ulama Union. By focusing on its role and contribution both in organizations and thinking. This research uses a descriptive qualitative type, with primary data from several supporting literature in the form of books and journals relevant to the initial research concept. The research process was carried out through several stages, namely, collecting data from various trusted sources relevant to the topic of discussion. Then, the data was collected and processed by reducing irrelevant data. Next, the data were analyzed using literature study techniques. This study found that the involvement of Shaikh Yusuf Al-Qaradawi was influential in forming the unity of world ulama, as seen from the substantial capacity of the International Union of Muslim Scholars (IUMS). As the leader at IUMS, Al-Qaradawi has dominant authority in controlling the mobility of the world's ulama. Apart from that, several of his thought products and fatwas have become the guidance of world ulama in dealing with contemporary problems.Keywords:Syaikh YusufAl-Qaradawi;Unity of Ummah; IUMS.